Preserving Paratenon in Acute Achilles Tendon Repair: A 5-Year Follow-Up - Mohammad Hossein Chegini Kord MD; Alireza Ebrahimi MD; Gregory R. Waryasz MD; Soheil Ashkani-Esfahani MD; Mohammad Razi MD (Foot & Ankle Orthopaedics)
Category: Sports; Trauma Introduction/Purpose: Achilles Tendon (AT) rupture is one of the most prevalent adult tendon injuries, with the incidence rate estimated to range between 7 to 40 in 100000 person-years. Although some surgical approaches involve incising or removing the Paratenon when repairing injured or degenerative tendons, an alternative perspective suggests preserving the paratenon during AT repair could potentially benefit healing through two proposed mechanisms: retaining the hematoma, which may contain factors with stem cell-like properties and reducing mechanical stress on the skin incision site. The aim of this study was to investigate the potential influence of Paratenon preservation on the outcomes of AT repair in a 5-year follow up study. Methods: After receiving IRB approval, we conducted a single-center study in Tehran, Iran, involving a consecutive series of 52 patients who sustained acute AT ruptures (less than 2 weeks from injury) and underwent a modified surgical technique performed by surgeons affiliated with the local institution. The technique involved careful skin incision while preserving the Paratenon intact and performing the tendon repair over the retained Paratenon (Figure 1). Patients were prospectively evaluated with a mean follow-up duration of 5 years (between 48 to 72 months). Functional outcomes were assessed using the Achilles Tendon Rupture Score (ATRS) and the American Orthopedic Foot and Ankle Society (AOFAS) rating scales in all patients at 6, 9, 18, and 36 months postoperatively. Two complementary follow-up visits at 12 and 24 months after the last visit were scheduled. Results: The mean AOFAS and ATRS scores were 83±4 and 85.7±3.1, respectively, by the 36-month follow-up visit. Approximately 90.1% of patients regained preinjury activity levels during the complementary follow-up visits, including 71.3% of professional athletes returning to prior recreation. Isokinetic testing revealed plantar flexion and dorsiflexion strength deficits of 83.7±5.1% and 87.8±3.6% compared to the uninjured sides at 3 months after the surgery. Calf muscle atrophy was minimal. While 19 patients reported initial activity-related pain, these symptoms resolved within 12 months. No wound complications, nerve injuries, or footwear issues occurred during the study period. Conclusion: Preserving the Paratenon during AT repair showed satisfactory functional and clinical outcomes without any case of the wound complications that are common after open repairs. These findings support the hypothesis that an intact Paratenon aids tendon healing and reduces complication rates. Retaining the Paratenon may also help mitigate the "bowstring" effect on the repaired Achilles tendon. This surgical technique warrants further investigation as a potential strategy for enhancing outcomes following AT ruptures.